ANALISIS PENGUKURAN KINERJA RUMAH SAKIT AL-IRSYAD DENGAN PENDEKATAN BALANCED SCORECARD - Ulaila, Tia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
This research is meant to measure the hospital performance by using balanced scorecard method. Balanced scorecard method is a comprehensive measurement which focuses on 4 perspectives i.e.: financial perspective, customerâs perspective, internal business process perspective, and growth and learning perspective. The data analysis technique is qualitative which is performed by using descriptive study. The research is conducted by taking primary and secondary data from Al-Irsyad Hospital. It can be concluded from the result of research which have been done by using Balanced Scorecard standard that Al-Irsyad Hospital is quite good, this is shown from the result of four perspectives analysis. Balanced Scorecard can give overall performance description of Al-Irsyad Hospital.Keywords: Balanced Scorecard, Financial Perspective, Customerâs Perspective, Internal Business Process Perspective, and Growth and Learning Perspective